EVALUATION OF COMMUNITY FINANCIAL PERFORMANCE AND WELFARE LEVEL OF MAKASSAR CITY - Baso, Baso R (Patria Artha Journal of Accounting dan Financial Reporting, 2018)
ABSTRACT This study aims to determine 1) the significance of the average difference in the financialperformance of Makassar City Govermment in the period of IAS and DIA period, and 2) thesignificance of the difference in the average welfare of society in Makassar in the period of IASand the periode DIA This research was conducted in Makassar, using secondary data, analytical techniqueused is the technique of analysis of difference test two average to variable of local financialperformance include independency ratio, effectiveness ratio, efficiency ratio and expediencyharmony ratio, and variable of society prosperity include indicator of income per capita,educational level and life expectancy of the community between the IAS period and the DIAperiod. The result of the research on the variable of regional finance performance shows thatthere is no significant difference of average of Makassar City govermment’s financialperformance in the period of IAS and the of DIA. While the results of research on the variablewelfare community shows that there are significant differences in the average welfare ofMakassar City periode IAS and The period of DIA in terms of income per capita, the number ofpeople who received education and life expectancy level.